The LIM Protein AJUBA is a Potential Oncogenic Target and Prognostic Marker in Human Cancer via Pan-Cancer Analysis - Song, Na; Liu, Jia; Zhang, Ke; Yang, Jie; Cui, Kai; Miao, Zhuang; Zhao, Feiyue; Meng, Hongjing; Chen, Lu; Chen, Chong; Li, Yushan; Shao, Minglong; et al. (Frontiers in Cell and Developmental Biology, 2022)
Purpose: The LIM (Lin-11, Isl1, MEC-3) domain protein AJUBA is involved in multiple biological functions, and its aberrant expression is related to the occurrence and progression of various cancers. However, there are no analytical studies on AJUBA in pan-cancer. Methods: We performed a comprehensive pan-cancer analysis and explored the potential oncogenic roles of AJUBA, including gene expression, genetic mutation, protein phosphorylation, clinical diagnostic biomarker, prognosis, and AJUBA-related immune infiltration based on The Cancer Genome Atlas and Genotype-Tissue Expression databases. Results: The results revealed that the expression of AJUBA highly correlated with poor clinical outcomes in patients with different types of cancer. Meanwhile, AJUBA expression was positively correlated with cancer-associated fibroblasts in many human cancers, such as breast invasive carcinoma, colon adenocarcinoma, brain lower-grade glioma, lung adenocarcinoma (LUAD), and ovarian serous cystadenocarcinoma (OV). Gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses showed that AJUBA is mainly involved in protein serine/threonine kinase activity, cell–cell junction, covalent chromatin modification, and Hippo signaling pathway. Conclusion: The pan-cancer study reveals the oncogenic roles of AJUBA and provides a comprehensive understanding of the molecular biological genetic information of AJUBA in various tumors.